Highly Effective Crosstalk Mitigation Method Using Counter-Propagation in Semiconductor Optical Amplifier for Remodulation WDM-PONs. (19th October 2014) - Pham, Quang Thai
Abstract : Remodulation-induced crosstalk mitigation in WDM-PON using remodulation approach is presented in this paper. Utilizing all-optical signal processing, the proposed method has been able to significantly improve system performance in terms of bit error rate (BER) and bit rate distance product. Moreover, the proposed method could be used for both baseband and modulated downstream electrical signals.